The Traffic Sign Detection Algorithm Based on Region of Interest Extraction and Double Filter - Yu, Dongxian; Kang, Jiatao; Cao, Zaihui; Nayyar, Anand (Recent Advances in Computer Science and Communications, 2021)
Objective: In order to solve the current traffic sign detection problem due to the interference of various complex factors, as it is difficult to effectively carry out the correct detection of traffic signs, a traffic sign detection algorithm based on the region of interest extraction and double filter is designed. Methods: First, in order to reduce environmental interference, the input image is preprocessed to enhance the main color of each logo. Secondly, in order to improve the extraction ability of Regions Of Interest, a Region Of Interest (ROI) detector based on Maximally Stable Extremal Regions (MSER) and Wave Equation (WE) is used, and candidate regions are selected through the ROI detector. Then, an effective HOG (Histogram of Oriented Gradient) descriptor is introduced as the detection feature of traffic signs, and SVM (Support Vector Machine) is used to classify them into traffic signs or background. Finally, the context-aware filter and the traffic light filter are used to further identify the false traffic signs and improve the detection accuracy. In the GTSDB database, three kinds of traffic signs, which are indicative, prohibited and dangerous, are tested. Results: The results show that the proposed algorithm has a higher detection accuracy and robustness compared with the current traffic sign recognition technology.
Keywords: wave equation